2016
DOI: 10.1371/journal.pone.0149474
|View full text |Cite
|
Sign up to set email alerts
|

Structural Study of Cell Attachment Peptide Derived from Laminin by Molecular Dynamics Simulation

Abstract: Peptides with cell attachment activity are beneficial component of biomaterials for tissue engineering. Conformational structure is one of the important factors for the biological activities. The EF1 peptide (DYATLQLQEGRLHFMFDLG) derived from laminin promotes cell spreading and cell attachment activity mediated by α2β1 integrin. Although the sequence of the EF2 peptide (DFATVQLRNGFPYFSYDLG) is homologous sequence to that of EF1, EF2 does not promote cell attachment activity. To determine whether there are stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…7,8 Since they promote diverse biologically relevant activities, including cell migration, neurite outgrowth, differentiation, and tumor angiogenesis and metastasis, they are a promising therapeutic target for tissue repair. [9][10][11] Several bioactive peptides from mouse laminin α1 chain were previously identified by screening the full-length protein using a library of synthetic peptides that span its entire amino acid sequence. Small peptides approximately 12 amino acids in length were synthesized, where each peptide consisted of an overlap with four amino acids with the preceding peptide.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Since they promote diverse biologically relevant activities, including cell migration, neurite outgrowth, differentiation, and tumor angiogenesis and metastasis, they are a promising therapeutic target for tissue repair. [9][10][11] Several bioactive peptides from mouse laminin α1 chain were previously identified by screening the full-length protein using a library of synthetic peptides that span its entire amino acid sequence. Small peptides approximately 12 amino acids in length were synthesized, where each peptide consisted of an overlap with four amino acids with the preceding peptide.…”
Section: Introductionmentioning
confidence: 99%
“…The data can be visualized by means of correlation maps calculation using the equation The covariance matrix map allows the identification of residue pairs with correlated and anticorrelated motion . The projections of the original structures onto the eigenvectors of the related principal components are represented as plots of the cross-correlation map. , …”
Section: Methodsmentioning
confidence: 99%
“…Formerly, we performed conformation analysis of peptides (EF1, sEF1 and EF2) in LG4 modules using molecular dynamics simulations. Our previous results showed that EF1 has hairpin-like structure (EF2 does not have), and we indicated relation between activities and the structure [6][7]. In this paper, we investigate dynamics behavior of EF1 and EF2 peptides at 300K and 1bar (NPT ensemble).…”
Section: Introductionmentioning
confidence: 91%